Classical and molecular cytogenetic analysis in head and neck squamous cell carcinomas - Veiga, Luciana CS [UNESP] (2003)
Head and neck carcinomas represent the sixth most frequent type of cancer in the world, and 90% are derived from squamous cells (HNSCC). In this study of 15 HNSCC cases, extensive aneuploidy was detected by G banding in most tumors. The most frequently observed numerical changes involved gain of a chromosome 22, and loss of chromosomes Y, 10, 17, and 19. The most frequent structural alteration was del(22)(q13.1). As compared to G-banding, fluorescence in situ hybridization (FISH) proved to be an effective technique for detecting aneuploidy. Interphase FISH with a chromosome 17 centromere probe disclosed a high frequency of monosomy for chromosome 17, in contrast with G-banding, by which clonal monosomy 17 was detected in only three of the tumors. Painting probes for chromosomes 5 and 16 were used to evaluate a selected series of HNSCC in which G-banding analysis had shown marker chromosomes. FISH analysis failed to confirm the origin of the marker chromosomes, but four out of five cases showed a significant loss of chromosomes 5. This difference between FISH and G-banding results may reflect the smaller number of metaphase analyzed as well as the criteria adopted for sorting these metaphases. Therefore results obtained solely by G-banding analysis should be considered with caution. Our data confirmed the involvement of chromosome 17 in head and neck squamous cell carcinomas.